Peculiar failure mechanisms in GaN power transistors. (November 2020) - Vanzi, M.; Mura, G.
Abstract: Commercial GaN power amplifiers for RF applications, made of a pair of discrete transistors for operation in Doherty configuration, failed during the HAST tests. Failure Analysis pointed out a layout-specific issue related to thermal expansion at the level of the field plates. Anyway, the search for initial degradation stages using Optical Beam Induced Resistance Change and Photon Emission Microscopy revealed a subtle second mechanism, involving Ga interdiffusion into the gate metal lines, coming from hollow pipes in GaN. Both mechanisms are discussed. Highlights: Power GaN HEMTs for RF applications failed during environmental tests THB and HAST. Field plate-related thermomechanical stress causes one of the two kinds of failures. Alignment of hollow GaN pipes and Gate fingers leads to leaky paths.